2005
DOI: 10.1007/s00125-005-0072-8
|View full text |Cite
|
Sign up to set email alerts
|

Visual acuity and perimetry as measures of visual function in diabetic macular oedema

Abstract: Aims/hypothesis: We examined to what extent visual acuity and perimetric sensitivity as measures of central and paracentral visual function would be useful for evaluating the presence and severity of diabetic macular oedema. Materials and methods: We evaluated 59 eyes of 59 diabetic patients by identifying the presence (n=20) or absence (n=39) of macular oedema on stereo fundus photographs. The area of oedema and its distance to the centre of the macula were measured. Ischaemic macular damage was quantified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 16 publications
1
13
0
1
Order By: Relevance
“…; Agardh et al. ), we found that CSMO was associated with very few, if any, significantly depressed points. The laser treatment reduced the thickness of the retina and lateral expansion of the oedema, but did not increase the number of depressed points.…”
Section: Discussionsupporting
confidence: 52%
“…; Agardh et al. ), we found that CSMO was associated with very few, if any, significantly depressed points. The laser treatment reduced the thickness of the retina and lateral expansion of the oedema, but did not increase the number of depressed points.…”
Section: Discussionsupporting
confidence: 52%
“…A study of human donor retinas demonstrated a 21% reduction of S-cones compared with medium-and long-wavelength cones [41]. SWAP has also been found to be abnormal in patients with DME, but the impairment appears to be caused by capillary damage rather than retinal thickening [42].…”
Section: Outer Retinal Functionmentioning
confidence: 99%
“…SWAP had a greater capability in detecting differences between the AMD groups and differences from normal, than SAP. Previous studies of blue-on-yellow perimetry in AMD [5], [6] did not compare results to SAP, however in patients with diabetes, sensitivity loss in the 10–2 visual field, due to structural change, was better detected by SWAP than SAP [23], [35], [36], [37]. The SWS pathway is vulnerable to a variety of retinal disease implying that SWS pathway sensitivity loss occurs at multiple sites of damage [38].…”
Section: Discussionmentioning
confidence: 99%